RETRACTED: The Influence Of Transformational Leadership, Motivation, Physical Work Environment And Job Stress On Employee Performance At Pt. Indonesian Trains(Persero) Daop 1 Jakarta Year 2019 - Larasati Ilyas; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research aims to determine and analyze the influence of transformational leadership, motivation, physical work environment and work stress on employee performance at PT. Indonesian Railways (Persero) Daop 1 Jakarta. This research data uses primary data in the form of a questionnaire to 101 employees of PT. Indonesian Railways (Persero) Daop 1 Jakarta. The data analysis technique uses multiple linear regression analysis and uses the SPSS 23 program. The research results show that there is an influence between Transformational Leadership (X1) on Employee Performance (Y). Then there is the influence of the Motivation variable (X2) on Employee Performance (Y). Likewise, for the Physical Work Environment variable (X3) there is an influence on Employee Performance (Y). Then the Job Stress variable (X4) also has an impact on Employee Performance (Y). Partially or simultaneously, it has a strong influence among the four variables, the most significant of which is the Motivation variable. The results of this research hope that companies can improve good leadership styles and a comfortable work environment so that they can support employee performance.